2023
DOI: 10.3390/biom13050852
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Induced Alternations of Adiponectin, Interleukin-8 and Indicators of Carbohydrate Metabolism in Males with Metabolic Syndrome

Abstract: Adiponectin (ADIPO) and interleukin-8 (IL-8) are proteins that play a significant, albeit opposing, role in metabolic syndrome (MetS). The reported data on the effect of physical activity on the levels of these hormones in the population of people with MetS are conflicting. The aim of the study was to evaluate the changes in hormone concentrations, insulin-resistance indices and body composition after two types of training. The study included 62 men with MetS (age 36.6 ± 6.9 years, body fat [BF] = 37.53 ± 4.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 77 publications
2
5
0
Order By: Relevance
“…During the observation period without planned exercises in our study, we confirmed an increase in ASP concentration compared to the 12-week intervention, both in the intervention group (EG2) and the CG. Such fluctuation may be attributed to increased carbohydrate and fat consumption in the diet of the examined men, as demonstrated in our previous work 31 . The observed upward trend in circulating ASP concentrations in CG may corroborate reports associated with the risk of ASP accumulation in the bodies of individuals with MetS and the ensuing metabolic consequences.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…During the observation period without planned exercises in our study, we confirmed an increase in ASP concentration compared to the 12-week intervention, both in the intervention group (EG2) and the CG. Such fluctuation may be attributed to increased carbohydrate and fat consumption in the diet of the examined men, as demonstrated in our previous work 31 . The observed upward trend in circulating ASP concentrations in CG may corroborate reports associated with the risk of ASP accumulation in the bodies of individuals with MetS and the ensuing metabolic consequences.…”
Section: Discussionsupporting
confidence: 67%
“…Such a mechanism may contribute to the progression of obesity and its associated metabolic disorders 16 , 17 . In the CG, despite the lack of intervention, we confirmed an increase in fat consumption in the diet 31 . The disease of obesity and its comorbidity with MetS, without interventions aimed at improving health status, lead to progressive hormonal, metabolic, psychological, and numerous other disorders 32 , 33 .…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations